Perfil metabólico de ratos adultos submetidos à restrição protéica na vida intrauterina e superalimentados durante a lactação - Coutinho, Grazielle Vitória Ponti (2012)
We investigated whether overfeeding during lactation following intrauterine protein restriction would cause adult-onset obesity and metabolic disorders. After birth, litters from dams fed with control (17% protein) and low protein (6% protein) diets were adjusted to a size of four (CO and LO groups, respectively) or eight (CC and LC groups, respectively) pups. All of the offspring were fed a diet containing 12% protein from the time of weaning until they were 90 d old. Compared to the CC and LC groups, the CO and LO groups had higher relative and absolute food intake, oxygen consumption and carbon dioxide production; lower brown adipose tissue weight and lipid content; but greater weight gain and white adipose tissues weight and lipid content. Compared to the CO and CC rats, the LC and LO rats exhibited higher relative food intake, brown adipose tissue weight and lipid content, reduced oxygen consumption, carbon dioxide production and spontaneous activity, but unaltered white adipose tissue weight and lipid content. Fasting serum glucose was similar between the groups. The area under the glucose curve was higher in the LO and CO rats than in the LC and CC rats. Basal insulinemia and homeostasis model assessment of insulin resistance (HOMA-IR) were lower in the LO group than in the other groups. The total area under the insulin curve for the LO rats was similar to the CC rats, and both were lower than the CO and LC rats. Kitt was higher in the LO, LC and CO groups than in the CC group. Thus, overfeeding during lactation increased visceral fat and, body mass, and it resulted in glucose intolerance by impairing pancreatic function or insulin resistance.